2018
DOI: 10.4103/0366-6999.226889
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Adipose-derived Mesenchymal Stem Cell Exosomes on Corneal Stromal Fibroblast Viability and Extracellular Matrix Synthesis

Abstract: Background:Corneal stromal cells (CSCs) are components of the corneal endothelial microenvironment that can be induced to form a functional tissue-engineered corneal endothelium. Adipose-derived mesenchymal stem cells (ADSCs) have been reported as an important component of regenerative medicine and cell therapy for corneal stromal damage. We have demonstrated that the treatment with ADSCs leads to phenotypic changes in CSCs in vitro. However, the underlying mechanisms of such ADSC-induced changes in CSCs remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“… 20 Exosomes contain complex molecular components, which include general and cell type specific lipids, proteins, mRNA, and miRNA, enabling them to function as vectorized, multisignaling devices. 27 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Exosomes contain complex molecular components, which include general and cell type specific lipids, proteins, mRNA, and miRNA, enabling them to function as vectorized, multisignaling devices. 27 29 …”
Section: Discussionmentioning
confidence: 99%
“…The bi-lipid membrane of exosomes can maintain the encapsulated proteins, messenger RNA (mRNA), and microRNA (miRNA) under stable conditions to exert lasting effect. 27 29 Therefore, they can be formulated as a topical gel or drop and can be locally administered. They can also be reprogrammed to be carriers for therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the treatment of MSC-derived EVs to corneal stromal cells (CSCs) induces the upregulation of MMPs and downregulation of ECM-related proteins such as collagens and fibronectin in CSCs. The findings indicate that adipose-MSCs might play an important role in the regulation of CSC viability through ECM remodeling, via EVs [ 195 ].…”
Section: Ev-driven Matrix Remodeling: Roles In Tissue Repair and Tmentioning
confidence: 99%
“…In a mouse model of hyperoxic-induced retinopathy, intravitreal injection of MSC-EXs partially preserved retinal vascular blood flow and improved the symptoms of retinal ischemia without immunosuppression [40]. Corneal stromal cells (CSCs) are involved in the formation of a functional corneal endothelium and they play a remarkable role in moderating the corneal endothelial microenvironment [41]. Shen et al indicated that AdMSC-EX treatment obviously promoted CSC proliferation in vitro, inhibited its apoptosis, triggered higher expression of collagen and fibronectin, and caused lower expression of matrix metalloproteinases [41].…”
Section: Eyesmentioning
confidence: 99%
“…Corneal stromal cells (CSCs) are involved in the formation of a functional corneal endothelium and they play a remarkable role in moderating the corneal endothelial microenvironment [41]. Shen et al indicated that AdMSC-EX treatment obviously promoted CSC proliferation in vitro, inhibited its apoptosis, triggered higher expression of collagen and fibronectin, and caused lower expression of matrix metalloproteinases [41]. Samaeekia et al demonstrated that human corneal MSC-derived EXs significantly increased the corneal wound healing rate (Ex vs. Control; 77.5% vs. 41.6%) in a murine model [42], providing a promising non-cellular therapeutic approach for ocular surface injury.…”
Section: Eyesmentioning
confidence: 99%